Diskursus Kredibilitas dan Pertimbangan Etika Pers dalam Proses Produksi Berita Viral #Justiceforaudrey di Liputan 6 Siang SCTV - Fran Celino Octhanto Bata; Umaimah Wahid (LUGAS Jurnal Komunikasi, 2020)
Viral events on social media are often made into the news. One of the social media viral events that made the news in mid-2019 was #JusticeforAudrey. Allegations of violence against Audrey made headlines in all mass media, including on Liputan 6 Siang SCTV. During April 2019, projections related to Audrey's coverage were submitted by producers every day. The news values that is the basis for determining the feasibility of an event to become news is no longer the priority of producers. This research paradigm is critical with a qualitative approach and uses the Fairclough Critical Discourse Analysis method. Theory of Political Economy Vincent Mosco explains the practice of viral news values is the practice of commodification of content and audiences. Viral social media events are considered attractive to internet users and expected to attract tv viewers. The practice of viral social media news is the commodification of content. Meanwhile, in the commodification of audiences, television news viewers in the form of rating & share are used as sales to advertisers, which in turn become an economic advantage for media corporations.